Juvenile Cellulitis in a Dachshund Puppy – A Case Report - Krishnanath, MR; Unny, N Madhvan; Pillai, Usha Narayana (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Juvenile cellulitis is an uncommon, idiopathic granulomatous and pustular disorder of the face, pinnae and submandibularlymph nodes (Miller et al., 2013). The condition is also called juvenile sterile granulomatous dermatitis and lymphadenitis,juvenile pyoderma, and puppy strangles.